Associations between sleep duration, sleep quality, and weight status in Chinese children and adolescents - Huan Chen; Li-Juan Wang; Fei Xin; Guo Liang; Yuan Chen (BMC, 2022)
Abstract Background and objective The high prevalence of obesity is a serious problem, and sleep is considered to be a factor for obesity. This study aimed to examine the relationship between sleep duration, sleep quality, and weight status among children and adolescents in China and to explore whether the relationship between sleep duration and weight status is independent of sleep quality. Sex and age differences were also explored. Methods A cross-sectional research was conducted among 2019 children and adolescents (1029 boys and 990 girls) aged 8-16 years in Shanghai. An open-question was used to obtain data on sleep duration, which was categorized into the following four groups based on the age-specific National Sleep Foundation Sleep Duration Recommendations: 1) very short, 2) short, 3) recommended, and 4) long. The Pittsburgh Sleep Quality Index was used to assess sleep quality. Weight and height were measured for all participants. The variable weight status was estimated with the Chinese children and adolescent age- and sex-specific body mass index (BMI) and was categorized into overweight/obesity and normal weight. Results Short sleep duration (7-8 and 6-7 h for 6-13 and 14-16 years old, respectively) significantly increased odds of overweight/obesity (OR = 1.32, 95% CI: 1.06-1.64) compared with that of the recommended sleep duration (9-11 and 8-10 h for 6-13 and 14-16 years old, respectively). The relationship between the two variables existed independent of sleep quality. No significant relationship was found between sleep quality and overweight/obesity of children and adolescents. Sleep quality (OR = 1.07, 95% CI: 1.01-1.14) and short sleep duration (OR = 1.51, 95% CI: 1.06-2.13) increased the risk for overweight/obesity among girls, whereas no significant relationships between sleep duration, sleep quality, and overweight/obesity were found among boys. Short sleep duration increased the risk of overweight/obesity in children aged 8-13 years (OR = 1.34, 95% CI: 1.05-1.71), independent of sleep quality, but no significant relationships between these two variables existed for adolescents aged 14-16 years. Conclusions Overall, short sleep duration increased the risks of overweight/obesity in children and adolescents in China, independent of sleep quality. This relationship is significant for girls and children aged 8-13 years instead of boys and adolescents aged 14-16 years. Interventions to extend the sleep duration of children and adolescents, especially girls and children aged 8-13 years in China, are necessary to improve their weight status.